2013
DOI: 10.4254/wjh.v5.i10.558
|View full text |Cite
|
Sign up to set email alerts
|

Rapid chromatographic method to decipher distinct alterations in lipid classes in NAFLD/NASH

Abstract: AIM:To establish a simple method to quantify lipid classes in liver diseases and to decipher the lipid profile in p62/IMP2-2/IGF2BP2-2 transgenic mice. METHODS:Liver-specific overexpression of the insulin-like growth factor 2 mRNA binding protein p62/ IMP2-2/IGF2BP2-2 was used as a model for steatosis. Steatohepatitis was induced by feeding a methioninecholine deficient diet. Steatosis was assessed histologically. For thin layer chromatographic analysis, lipids were extracted from freeze-dried tissues by hexan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 52 publications
(67 reference statements)
2
28
0
2
Order By: Relevance
“…The p62-induced steatosis is characterized by an increase in almost all lipid classes, with the most distinct effect on triglycerides ( 26 ). Accordingly, we here observed an elevated abundance of almost all fatty acids ( Table 1 ).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The p62-induced steatosis is characterized by an increase in almost all lipid classes, with the most distinct effect on triglycerides ( 26 ). Accordingly, we here observed an elevated abundance of almost all fatty acids ( Table 1 ).…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, p62 has been shown to promote NASH development ( 25 ). Most lipid species are elevated in p62-induced steatosis, with triglycerides showing the strongest increase ( 26 ). p62 was originally identifi ed as an autoantigen overexpressed in about one-third to two-thirds of HCC patients and correlates with poor outcome (27)(28)(29)(30).…”
Section: Protein Isolation and Analysis By Western Blotmentioning
confidence: 99%
“…Only physiological roles have been described for IMP2, which is required for proper nerve cell migration and morphology during development by controlling cytoskeletal remodeling and dynamics (reviewed in [17] ). We recently reported that mice with liver-specific overexpression of p62 develop a fatty liver and show increased development towards NASH-induced fibrosis [4,18,19] . This amplification of an inflammatory response was observed in a feeding model that omitted dietary cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of fatty acids in the liver has emerged as a critical factor promoting the development of non-alcoholic steatohepatitis (NASH) and potentially HCC [3][4][5][6][7] , with monounsaturated fatty acids (MUFA) implicated in a pathophysiological role [6,8] . Recent observations also highlighted the accumulation of free cholesterol as an important trigger for the progression from simple steatosis to severe NASH [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Идентификацию хроматографических пиков про-водили с использованием индексов удерживания ECL (Christie, 1988). Содержание отдельных классов липидов в сравнении со стандартами анализировали методом тон-кослойной хроматографии на аналитических пластинах «Sorbfil» с использованием системы растворителей гексан : диэтиловый эфир -1 : 1 (по объему) с добавлением 0,1 % уксусной кислоты в качестве элюента (Laggai et al, 2013).…”
Section: материалы и методыunclassified